Sobreprotección de los padres en el desarrollo interpersonal de los niños y niñas de educación inicial ii, subnivel i de la escuela fisco misional básica “Dr. Gabriel García Moreno”, parroquia la matriz, cantón Guano, provincia de Chimborazo periodo 2017-2018 - Altamirano Álvarez, Mercedes Catalina (2018)
The objective of the present investigation was to determine the overprotection of the parents in the interpersonal development of the children of Initial Education II, Sub-level I of the Basic School "Dr. Gabriel Garcia Moreno ", Parish La Matriz, Canton Guano, Province of Chimborazo period 2017-2018". Theoretically, the work was based on the independent variable, the overprotection and the dependent variable, the interpersonal development, which were supported by their respective bibliographies. Methodologically, the design is non-experimental, field-based, the level is diagnostic-exploratory, the population with which it worked was 25 children of Initial II Sub-level I, the sample was not probabilistic because its sampling was random and intentional, the technique used was the Observation and the instrument the observation file, the same one that served us as a reference for the analysis and interpretation of data, where it could be concluded that the overprotection of the parents is high since the children have different characteristics of overprotection as dependence, they are shy, they have self-esteem problems, they are insecure and do not interact with others because they are afraid of not doing well, it is recommended to hold a workshop for parents and teachers where they help to know the consequences it brings about overprotection in the future of their children, where interpersonal relationships are also reinforced.